2024
DOI: 10.31580/jmi.v7i3.1600
|View full text |Cite
|
Sign up to set email alerts
|

Black Friday and Consumer Misbehavior: A Qualitative Analysis of Pakistan’s Black Friday Sale

Abstract: The purpose of the research was to observe, explore, and analyze the behaviours and misbehaviours of Pakistani consumers during the Black Friday sale. The factors that lead the consumers to misbehave in the discounted event were observed and explored as well. This study undertook the consumers who were shopping during the Black Friday sale. The observations, interviews, and images were collected to analyze. The data analysis was done by coding major themes. By using these factors a conceptual framework of fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In recent research, Nawaz and Khan (2020) found Pakistani consumers misbehaving during the Black Friday sale. Similarly, during a sale event in Pakistan, women were found fighting over discounted clothes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, Nawaz and Khan (2020) found Pakistani consumers misbehaving during the Black Friday sale. Similarly, during a sale event in Pakistan, women were found fighting over discounted clothes.…”
Section: Introductionmentioning
confidence: 99%